Investigating visitors' perception of smart city dimensions for city branding in Hong Kong. Issue 4 (11th November 2019) - Chan, Chung Shing; Peters, Mike; Pikkemaat, Birgit
Abstract : Purpose: The purpose of this paper is to understand the perceptions of visitors in terms of multiple aspects of smart cities to allow wise decisions to be made about smart tourist destinations by municipal governments and tourism authorities. Design/methodology/approach: This study takes a sample of inbound visitors ( n =205) from Hong Kong as an empirical questionnaire-based survey on visitors' perceptions of these smart city attributes, which are collected from literature, and framed in Cohen's Smart City Wheel. Findings: This paper identifies the distinctive factors for branding Hong Kong as a smart city. The results from the factor analysis identify four factors for determining what a smart city is from the perspective of visitors, namely, the quality of a smart society: energy consumption in an urban environment, smart city governance and smart city livelihood. The first two factors further become the determinants of a successful smart city brand considered by visitors, which contribute to their locational decisions and thus the strategies and policies of smart destination branding. Research limitations/implications: The results obtained can serve as insights for tourism policy makers and destination marketers when considering significant information and communication technology, or other smart and sustainable attributes for city branding (e.g. Buhalis and Amaranggana, 2014; Marine-Roig and Anton Clavé, 2015), as well as common investment and resource allocation for shared benefits in similar metropolises. Practical implications: The smartness factors represent important dimensions of urban smartness as prioritized areas for further development, innovation and marketing of tourism industries and enterprises in Hong Kong, as a mature urban destination incorporating the branding of a proposed smart district as a strategy of urban development. Originality/value: Smart urban development and tourism development have increasingly become inseparable, especially when visitors utilize cities as tourist destinations but share other urban resources and spaces with local citizens. Unlike the development of smart tourist attractions, smart tourist destinations should have a wider scope of smartness. A smart tourist destination may carry similar and overlapping characteristics of smart cities, which may be interpreted by visitors and may eventually affect their perceived image of a city.